Analysis of village head performance in public services: a case study in percut village district percut Sei Tuan - Barus, Rehia K. Isabella; Batubara, Beby Masitho; Harahap, Nurhayati (Penerbit Universiti Kebangsaan Malaysia, 2020)
According to Law No. 25 of 2009 public service is an activity or series of activities in the framework of meeting service needs in accordance with statutory regulations for every citizen of the country and residents, for goods, services, and / or administrative services provided by public service providersurpose of this research is to find out that public services have been carried out in accordance with existing regulations and to find out what actions the village head has taken to produce excellent performance as the quality of public services of the chief in order to guarantee quality services, complete, easily affordable, and measurable. This type of research uses descriptive qualitative research. The data is obtained using a qualitative historical approach and the research process is done naturally and naturally by forming a cycle and focuses the object under study based on field research and the farm of reference. The results of this study indicate that the performance of the village head in the implementation of public services has not gone well because there are still many people who complained about the length of time when completing their identity card (KTP) or family card (KK). The performance of the village head in the implementation of public services has not been going well because there are still many people who complain about the length of time it has been completed when handling administration problem.